Herd Protection against Meningococcal Disease through Vaccination - Stephen A. Clark; Ray Borrow (Microorganisms, 2020)
Reduction in the transmission of Neisseria meningitidis within a population results in fewer invasive disease cases. Vaccination with meningococcal vaccines composed of high weight capsular polysaccharide without carrier proteins has minimal effect against carriage or the acquisition of carriage. Conjugate vaccines, however, elicit an enhanced immune response which serves to reduce carriage acquisition and hinder onwards transmission. Since the 1990s, several meningococcal conjugate vaccines have been developed and, when used in age groups associated with higher carriage, they have been shown to provide indirect protection to unvaccinated cohorts. This herd protective effect is important in enhancing the efficiency and impact of vaccination. Studies are ongoing to assess the effect of protein-based group B vaccines on carriage; however, current data cast doubt on their ability to reduce transmission.